The Identification of Metal Ion Ligand-Binding Residues by Adding the Reclassified Relative Solvent Accessibility - Hu, Xiuzhen; Feng, Zhenxing; Zhang, Xiaojin; Liu, Liu; Wang, Shan (Frontiers in Genetics, 2020)
Abstract: Many proteins realize their special functions by binding with specific metal ion ligands in life process of cells. To correctly identify metal ion ligand binding residues is valuable for the human health and the design of molecular drug. However, it is still a challenging work to precisely identify these residues up to now. We presented an improved computational approach for predicting the binding residues of 10 metal ion ligands (Zn , Na + and K + ) by adding reclassified relative solvent accessibility. The best accuracy of 5-fold cross-validation was higher than 77.9%, which was about 16% higher than the previous result on the same dataset. It was found that different reclassification of the relative solvent accessibility information can make different contributions to the identification of specific ligand binding residues. Our study provided an additional understanding of relative solvent accessibility on the identification of metal ion ligand binding residues.